2021
DOI: 10.1007/s10792-021-01850-w
|View full text |Cite
|
Sign up to set email alerts
|

Refractive outcome and tomographic changes after Descemet membrane endothelial keratoplasty in pseudophakic eyes with Fuchs’ endothelial dystrophy

Abstract: Purpose To analyze refractive and topographic changes secondary to Descemet membrane endothelial keratoplasty (DMEK) in pseudophakic eyes with Fuchs’ endothelial dystrophy (FED). Methods Eighty-seven pseudophakic eyes of 74 patients who underwent subsequent DMEK surgery for corneal endothelial decompensation and associated visual impairment were included. Median post-operative follow-up time was 12 months (range: 3–26 months). Main outcome measures were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…The pooled estimate for the mean refractive outcomes of all 29 studies after DMEK was +0.43 diopters (D) (95% CI, 0.31-0.55) (Figure 2). 11,20–47 We observed substantial variation between the reported results, with about I 2 = 82% of the overall variability being attributed to heterogeneity between studies. Twenty-seven studies found a hyperopic shift after DMEK (Figure 3).…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…The pooled estimate for the mean refractive outcomes of all 29 studies after DMEK was +0.43 diopters (D) (95% CI, 0.31-0.55) (Figure 2). 11,20–47 We observed substantial variation between the reported results, with about I 2 = 82% of the overall variability being attributed to heterogeneity between studies. Twenty-seven studies found a hyperopic shift after DMEK (Figure 3).…”
Section: Resultsmentioning
confidence: 82%
“…27 Although no information on subjective refraction, astigmatism, or anterior topography was available in 31% (9 of 29) of studies, 41% (12 of 29) of studies observed no differences in preoperative and postoperative refractive cylinder or astigmatism. 21,22,24,25,27,33,35,36,38,42 In 8 (27.6%) studies with tomographic analysis, however, there was a statistically significant steepening of posterior corneal topography. 20,21,23,24,39,41,42,46 In a study of 87 pseudophakic eyes undergoing DMEK, Agha et al reported that postoperative changes were mainly observed in the posterior corneal surface, with a statistically significant reduction of posterior corneal astigmatism from 0.59 ± 0.56 D to 0.39 ± 0.27 D. 24 Moreover, the authors observed an increase in the number of eyes exhibiting an against-the-rule astigmatism from 42.8% to 73.6%, although the proportion of eyes with with-the-rule and oblique astigmatism decreased after DMEK.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…10–13 The hyperopic shift after DMEK is a frequently described phenomenon, observed in standalone DMEK procedure and in the DMEK triple procedure. 11–24…”
mentioning
confidence: 99%